Correction: Near infrared activation of an anticancer PtIV complex by Tm-doped upconversion nanoparticles. Issue 59 (4th July 2016) - Ruggiero, Emmanuel; Hernández-Gil, Javier; Mareque-Rivas, Juan C.; Salassa, Luca
Abstract : Correction for 'Near infrared activation of an anticancer Pt IV complex by Tm-doped upconversion nanoparticles' by Emmanuel Ruggiero et al., Chem. Commun., 2015, 51, 2091–2094.